REVISIÓN DE LAS LYCOPODIACEAE (EMBRYOPSIDA, LYCOPODIIDAE) DE ARGENTINA Y URUGUAY - Arana, Marcelo D.; Øllgaard, Benjamin (Darwiniana, 2012)
A review of the Lycopodiaceae from Argentina and Uruguay, based on the study of relevant collections from herbaria as well as literature, is presented, according to the new classification of 16 genera grouped into three subfamilies. The family is represented by nine genera and 23 species; all taxa are described and at least one species of each subfamily is illustrated; one species (Huperzia saururoides) is lectotypified and three new synonyms are proposed: Austrolycopodium assurgens under Austrolycopodium erectum, Lycopodium sanctae-barbarae under Phlegmariurus saururus and Urostachys selago var. aschersonianus under Huperzia saururoides. Lycopodiella alopecuroides and Phlegmariurus subulatus are excluded from the studied area. Keys for all taxa are provided, as well as the relevant synonyms and a synthesis of the ecology and distribution. The most diverse genera are Phlegmariurus (seven species) and Austrolycopodium (five species). In Argentina, the family is represented by 22 species distributed in the three subfamilies. The northwestern region is the richest area of the country, with nine species. In Uruguay the family is represented by the subfamily Lycopodielloideae, with four species belonging to the genera Lycopodiella (two species), Palhinhaea (one species) and Pseudolycopodiella, represented by Pseudolycopodiella meridionalis. The latter, Palhinhaea camporum, and Huperzia fuegiana s. str. are new records for Argentina. Se presenta una revisión de las Lycopodiaceae de Argentina y Uruguay basada en el estudio de las colecciones relevantes de los herbarios argentinos y uruguayos, así como de la literatura, acorde a la nueva clasificación de 16 géneros distribuidos en tres subfamilias. La familia está representada por nueve géneros y 23 especies; se describen todos los taxones y se ilustra al menos una especie de cada subfamilia. Se lectotipifica una especie (Huperzia saururoides) y se proponen tres nuevos sinónimos: Austrolycopodium assurgens bajo Austrolycopodium erectum, Lycopodium sanctae-barbarae bajo Phlegmariurus saururus y Urostachys selago var. aschersonianus bajo Huperzia saururoides. Se excluye del área de estudio a Lycopodiella alopecuroides y Phlegmariurus subulatus. Se proveen claves para todos los taxones, la sinonimia relevante y una síntesis de la ecología y la distribución. Los géneros más diversos son Phlegmariurus (siete especies) y Austrolycopodium (cinco especies). En Argentina la familia está representada por 22 especies distribuidas en las tres subfamilias. La región con mayor riqueza es el noroeste, con nueve especies. En Uruguay la familia está representada por la subfamilia Lycopodielloideae, con cuatro especies pertenecientes a los géneros Lycopodiella (dos especies), Palhinhaea (una especie) y Pseudolycopodiella, representado por Pseudolycopodiella meridionalis. Esta última, Palhinhaea camporum y Huperzia fuegiana s. str. son nuevos registros para Argentina.